Model-Model Quality Manajemen Pendidikan - Suprihatin Suprihatin; Sakiyem Sakiyem (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2023)
Quality is the ability of a product or service to meet customer needs. This article aims to: (1) determine the implementation of TQM in educational institutions more effectively and efficiently; (2) knowing the benefits obtained in improving quality continuously through implementing TQM in educational institutions. This research uses a literature study research method. Data collection techniques by collecting several previous studies. Previous research that has been collected is then compiled, analyzed and concluded in order to obtain conclusions regarding quality models of educational management. The conclusion in this research can be drawn that Total Quality Management (TQM) refers to a quality emphasis that covers the entire organization, from suppliers to customers. Implementation of Total Quality Management (TQM) in educational institutions, namely: continuous improvement; determine Quality Standards (Quality assurance); cultural change (change of culture); organizational change (upside-downorganization); and maintaining relationships with customers (keeping close to the customer). To support the implementation of TQM, an implementation strategy is needed, namely the Preparation Phase, Planning Phase and Implementation Phase. The success or failure of TQM implementation really depends on the commitment and cooperation of all elements of the educational institution, from top management to staff level.